The relationship between multi-dimensional production factors and economic growth: A study on the formation factors of economic differences - Chen, Meishan (Transactions on Economics, Business and Management Research, 2024)
Since the beginning of this century, China’s regional economic development has shown a typical dual structure characteristics, and the uneven development of regional economy has become the main resistance to the high-quality development of China’s economy. The formation of this dual structure is closely related to the unbalanced distribution of foreign investment in financial capital and high-quality labor force in human capital. Based on the panel data from 2000 to 2019, this paper conducts a regression analysis on financial capital and human capital, and obtains the proportion of their contribution to the economy, in which the proportion of foreign direct investment is the largest, followed by the proportion of labor population. At the same time, the high-quality labor force in developed regions contributes more to the economy than that in less-developed regions.